Élites e identidades: una visión de la sociedad meridana de la segunda mitad del siglo XIX - Várguez Pasos, Luis A. (El Colegio de México, A.C., 2002)
In this paper the author sets out to analyze the different elements that influenced the conformation of the identity of the elite that dominated Mérida's society, in Yucatan, during the second half of the  nineteenth century.  This elite was composed of Spaniards that established themselves in this city, and of Yucatecans of Spanish descent that were born there. Throughout this period, the  members of this elite dominated the  economy,  politics and culture  of  Yucatan, a domination that lasted into the first decades of the twentieth century.